Service quality models: a review - Seth, Nitin; Deshmukh, S.G; Vrat, Prem (The International journal of quality & reliability management, 2005)
Purpose - The main objective of this paper is to critically appraise various service quality models and identify issues for future research based on the critical analysis of literature.Design methodology approach - The paper critically examines 19 different service quality models reported in the literature. The critical review of the different service quality models is intended to derive linkage between them, and highlight the area for further research.Findings - The review of various service quality model revealed that the service quality outcome and measurement is dependent on type of service setting, situation, time, need etc factors. In addition to this even the customer's expectations towards particular services are also changing with respect to factors like time, increase in the number of encounters with a particular service, competitive environment, etc. This paper provides a rich agenda for future research in the subject.Research limitations implications - This research developed a linkage between the different service quality models.Practical implications - The growth of literature in the field of service quality seems to have developed sequentially, providing a continuous updating and learning from the findings observations of predecessors. This paper provides new directions to service quality researchers.Originality value - This paper explores new directions in service quality research and offers practical help to researchers and practitioners in providing a direction for service quality improvement.